Records of The Colony of New Plymouth 173 (1856) - (:unkn) unknown (My University, 1676)
Prohibited the selling, bartering, and giving of arms or ammunition to "any Indian," punishable by death.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES